DEVELOPMENT OF A MICROSOFT ACCESS-BASED ADMINISTRATIVE INFORMATION SYSTEM FOR GUIDANCE AND COUNSELING (E-BK) AT SMK NEGERI 2 MAJENE - Sabriani Sabriani; Abdul Saman; Farida Aryani (Jurnal Konseling Pendidikan Islam, 2026)
The main problems in this study are (1) How is the description of the needs of BK teachers regarding the E-BK administration information system based on Microsoft Access at SMK Negeri Majene. (2) How is the prototype of the E-BK administration information system based on Microsoft Access at SMK Negeri Majene. (3) How is the level of validity of the E-BK administration information system based on Microsoft Access at SMK Negeri Majene. (4) How is the practicality of the E-BK administration information system based on Microsoft Access at SMK Negeri Majene. This study was conducted by describing the R&D (Research & Development) approach using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) model. This research was conducted at SMK Negeri 2 Majene. The subjects of this study were 7 BK teachers and 10 students. Data collection techniques were by interview, observation and a trial questionnaire. The objectives of this study were (1) To describe the level of need for an E-BK administrative information system based on Microsoft Access at SMK Negeri Majene. (2) To understand the prototype of an E-BK administrative information system based on Microsoft Access at SMK Negeri Majene. (3) To measure the validity of an E-BK administrative information system based on Microsoft Access at SMK Negeri Majene. (4) To determine the level of practicality of an E-BK administrative information system based on Microsoft Access at SMK Negeri Majene. The results of the study indicate that (1) BK teachers need an administration system that can facilitate service recording, as well as student data management. (2) The prototype system developed contains student data input features, a simple and easy-to-use BK service recording. (3) The validation results show that the system has a high validation level with an average assessment of 90% by material experts and media experts. (4) The practicality test shows that this system is very helpful and easy to use by BK teachers, with a practicality score reaching 85%. Thus, the E-BK system based on Microsoft Access is declared valid and practical to be used as a tool in managing the administration of guidance and counselling services at SMK Negeri 2 Majene.